Radiation Quality-Dependent Progressive Increase in Oxidative DNA Damage and Intestinal Tumorigenesis in Apc1638N/+ Mice - Kamendra Kumar; Santosh Kumar; Jerry Angdisen; Kamal Datta; Albert J. Fornace; Shubhankar Suman (Current Oncology)
Exposure to high-linear energy transfer (LET) heavy ions, such as 28Si, poses a significant cancer risk for astronauts. While previous studies have linked high-LET radiation exposure to persistent oxidative stress and dysregulated stress responses in intestinal crypt cells with an increased risk of tumorigenesis, the relationship between IR-induced oxidative DNA damage and intestinal cancer risk remains incompletely understood. Here, we investigated the time-dependent effects of 28Si-ion radiation on intestinal tumorigenesis and oxidative DNA damage in Apc1638N/+ mice, a model for human intestinal cancer predisposition. Male Apc1638N/+ mice were exposed to 10 cGy of either γ-rays (low-LET) or 28Si-ions (high-LET), and intestinal tumor burden was assessed at 60 and 150 days post-irradiation. While both radiation groups showed modest, non-significant tumor increases at 60 days, 28Si-irradiated mice exhibited an approximately 2.5-fold increase in tumor incidence by 150 days, with a higher incidence of invasive carcinomas compared to γ and sham groups. Serum 8-OxodG levels, a marker of systemic oxidative stress, were significantly elevated in the 28Si-ion group, correlating with increased intestinal 8-OxodG staining. Additionally, assessment of the proliferation marker Cyclin D1 and metaplasia marker Guanylyl Cyclase C (GUCY2C) also revealed significant crypt cell hyperproliferation accompanied by increased metaplasia in 28Si-exposed mouse intestines. Positive correlations between serum 8-OxodG and tumor-associated endpoints provide compelling evidence that exposure to 28Si-ions induces progressive intestinal tumorigenesis through sustained oxidative DNA damage, crypt cell hyperproliferation, and metaplastic transformation. This study provides evidence in support of the radiation quality-dependent progressive increase in systemic and intestinal levels of 8-OxodG during intestinal carcinogenesis. Moreover, the progressive increase in oxidative DNA damage and simultaneous increase in oncogenic events after 28Si exposure also suggest that non-targeted effects might be a significant player in space radiation-induced intestinal cancer development. The correlation between serum 8-OxodG and oncogenic endpoints supports its potential utility as a predictive biomarker of high-LET IR-induced intestinal carcinogenesis, with implications for astronaut health risk monitoring during long-duration space missions.